2014
DOI: 10.1111/1567-1364.12219
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin promotes ATP-binding cassette transporter-dependent sterol uptake in yeast

Abstract: Sterol uptake in fungi is a multistep process that involves interaction between external sterols and the cell wall, incorporation of sterol molecules into the plasma membrane, and subsequent integration into intracellular membranes for turnover. ATP-binding cassette (ABC) transporters have been implicated in sterol uptake, but key features of their activity remain to be elucidated. Here, we apply fluorescent cholesterol (NBD-cholesterol) to monitor sterol uptake under anaerobic and aerobic conditions in two fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In the yeast Candida albicans , a subfamily member (Cdr3p) has been identified that exhibits an inward-directed phospholipid translocase activity. Some yeast ABC transporters (Aus1p and Pdr11p in S. cerevisiae; Aus1p in Candida glabrata ) facilitate exogenous sterol uptake [143148]. Three Arabidopsis proteins, TGD1-3, are proposed to form an ABC transporter complex in the inner envelope of the chloroplast that imports PA into the inside of the chloroplast for the synthesis of thylakoid lipids [149, 150].…”
Section: Control Of Transbilayer Lipid Asymmetry By Atp-driven Lipmentioning
confidence: 99%
“…In the yeast Candida albicans , a subfamily member (Cdr3p) has been identified that exhibits an inward-directed phospholipid translocase activity. Some yeast ABC transporters (Aus1p and Pdr11p in S. cerevisiae; Aus1p in Candida glabrata ) facilitate exogenous sterol uptake [143148]. Three Arabidopsis proteins, TGD1-3, are proposed to form an ABC transporter complex in the inner envelope of the chloroplast that imports PA into the inside of the chloroplast for the synthesis of thylakoid lipids [149, 150].…”
Section: Control Of Transbilayer Lipid Asymmetry By Atp-driven Lipmentioning
confidence: 99%
“…In both strains, the number of expressing cells and intensity of the expression signal varied substantially for Pdr11p upon galactose induction. Several studies report similar results of heterogeneous expression within the cell culture for other proteins expressed from multicopy plasmids [ 11 , 31 33 ]. A likely reason is fluctuating plasmid copy numbers within the cell population [ 34 ].…”
Section: Discussionmentioning
confidence: 67%
“…Many ABC transporters have been shown to possess intrinsic ATPase activity that is stimulated in the presence of transported substrates [ 1 , 24 , 30 ]. As sterol uptake is mediated by Pdr11p [ 4 ] and facilitated by albumin [ 11 ], we tested the effect of ergosterol, cholesterol, and albumin on ATPase activity. Neither ergosterol nor cholesterol in absence and presence of albumin stimulated the ATPase activity of purified Pdr11p ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches rely on application of fluorescently labelled sterol analogues, which however carry bulky chemical groups that can alter sterol behavior (Sezgin et al, 2016). Moreover, yeast cells only take them up in specific mutant backgrounds or growth conditions (Jacquier and Schneiter, 2012;Marek et al, 2014). Domain 4 (D4) of the bacterial toxin perfringolysin O (PFO), which binds membranes containing ≥30 mol% sterols and can be expressed in cells with no obvious toxicity, offers an interesting alternative (Shimada et al, 2002).…”
Section: Introductionmentioning
confidence: 99%